Improved workability and mechanical properties of cement grouting materials by carbon nanotubes coated with fly ash - Jiang, Jun; Sun, Houwei; Wang, Guoyuan; Deng, Xiansong; Li, Xiaoliang; Fan, Wenbo; Liu, Zhiqiang (Frontiers in Materials, 2025)
Carbon nanotubes (CNTs) modified cement provides a new way to develop high performance cement grouting materials. However, laboratory-grade CNTs are extremely costly (about 100 times the cost of industrial-grade CNTs) and have poor dispersion stability due to strong van der Waals forces at the nanoscale, which easily cause agglomeration. In addition, the time and energy consumption of CNTs dispersion and the problem of reaggregation further limit their application in engineering. Therefore, a novel dispersion method for CNTs was proposed in this paper. The proposed coating dispersion method not only achieved a good dispersion of CNTs on the surface of fly ash (FA), but also reduced the structural damage of CNTs during the dispersion process. At the same time, a strong covalent bond was formed between CNTs and FA, which effectively alleviated the reagglomeration problem of CNTs. Secondly, the workability and mechanical properties of cement grouting materials reinforced by CNTs coated with FA were studied through laboratory tests. The test results showed that compared with ordinary cement slurry, the fluidity and compressive strength were increased by 3.5%–11.6% and 2.09–32.87% after replacing part of cement with FA coated with CNTs. Finally, the mechanism of CNTs' influence on the microstructure of the grouting material was studied through the microcharacterization test. The results showed that CNTs coated on the FA surface produced nucleation effect and played a bridging role, promoted hydration reaction and improved the cement-FA interface transition zone (ITZ). In addition, CNTs coating FA effectively improved the energy absorption effect of the cement matrix, resulting in changes in the micro-roughness of the fracture surface of the sample.